ANALYSIS OF MATERNAL HEALTH LITERACY TOWARD ACCEPTANCE OF CONGENITAL HYPOTHYROID SCREENING - Ayu, Anugrah; Jalaluddin, Syatirah; Saharuddin; Anastasia, Rizka; Dahlan, Muh. (Universitas Islam Negeri Alauddin Makassar, 2025)
The condition of decreased function or malfunction of the thyroid gland in newborns is known as congenital hypothyroidism, this condition causes a child to experience problems in their growth period and is likely to experience mental retradation which will affect their physical and intellectual development. The screening of every newborn is inseparable from the approval and acceptance of parents, therefore it is very necessary for parents to have a level of health literacy towards health actions. This study aims to determine the relationship between maternal health literacy and acceptance of congenital hypothyroid screening at RSIA Ananda Makassar. The type of research used is quantitative with a Cross Sectional research design The population in this study were Trimester III pregnant women both primigravida and multigravida who did antenatal care (ANC) at the Hospital. The sampling technique used purposive sampling method, namely the selection of samples based on the researcher's consideration in accordance with the predetermined inclusion and exclusion criteria. The sample size was determined based on the Slovin formula, so that the number of samples in this study was 100 Data analysis using the Statitical Package For The Social Sciences (SPSS) 26. Data collection techniques using primary data, namely by distributing questionnaires. The results showed a p value of 0.004 <0.05 (significant value). There is a relationship between maternal health literacy and acceptance of congenital hypothyroid screening measures at RSIA Ananda Makassar in 2023.